Geographical distribution and evolutionary divergence times of Asian populations of the brine shrimp Artemia (Crustacea, Anostraca). (3rd March 2015) - Eimanifar, Amin; Van Stappen, Gilbert; Wink, Michael
<x xml:space="preserve">Abstract</x> The brine shrimp Artemia represents a widespread genus of microcrustaceans adapted to hypersaline environments. The species of this genus have been the subject of numerous phylogenetic studies, but many open questions remain, especially for Eurasian Artemia lineages. Artemia sinica Cai, 1989 and Artemia tibetiana have a restricted geographical distribution, whereas the Eurasian haplotype complex (EHC) and especially Artemia urmiana Günther, 1899 show wider ranges. We examined the geographic distribution, evolutionary age, and historical demography of the Asian Artemia lineages (A. urmiana, A. sinica, A. tibetiana, and the Eurasian haplotype complex) using samples from 39 geographical localities and based on the nucleotide sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene. Asian Artemia taxa clusters into four distinctive clades with high nodal support, consisting of 69 unique haplotypes. A star‐like haplotype pattern was visible in EHC lineages (comprising pathenogenetic populations), which were genetically close to two sexual species, A. urmiana and A. tibetiana. The Bayesian approach of molecular clock estimation indicated that A. sinica had already diverged in the late Miocene (19.99 Mya), whereas A. urmiana, A. tibetiana, and EHC shared a common ancestor in the late Pliocene (5.41 Mya). Neutrality tests indicated a recent population expansion in A. urmiana and EHC lineages. The diversification within A. urmiana and EHC lineages occurred in the Pleistocene (1.72 Mya) and Holocene (0.84 Mya), respectively. Overall, these results suggest a much longer evolutionary history of A. sinica and the possible evolutionary origin of EHC lineages from Asian sexual ancestors. Our findings point to the importance of species structure and divergence time variations of Asian Artemia, highlighting interspecific diversification and range expansion of local species in Asia. © 2015 The Linnean Society of London